2018
DOI: 10.11118/actaun201866030803
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Employee Development in Agricultural Companies on Commitment, Loyalty and Performance

Abstract: Employees in agricultural companies are aware of the necessity to learn and develop; hence it is essentially easier for the agricultural companies to encourage their employees to engage in these processes. Regardless the awareness of the employees concerning the development, the organisational features of the agricultural companies, which influence the development of the employees, needs to be taken into account. The aim of the paper is to identify the attitude of surveyed agriculture organisations towards emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, the studies also suggest that the impact of financial awards is significantly stronger than non-financial rewards. Employees in labor-intensive domains are less motivated with non-financial rewards than other sectors (Urbancová & Vnoučková, 2018;Whitener, 2001). The association between non-financial rewards and motivation also varies according to age and income group.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the studies also suggest that the impact of financial awards is significantly stronger than non-financial rewards. Employees in labor-intensive domains are less motivated with non-financial rewards than other sectors (Urbancová & Vnoučková, 2018;Whitener, 2001). The association between non-financial rewards and motivation also varies according to age and income group.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%
“…Many past studies based on empirical results have concluded a positive association between "financial rewards, commitment, and loyalty (Kreisman, 2002;Urbancová & Vnoučková, 2018). While Kurdi, Alshurideh & Alnaser (2020) also found that financial rewards promote employee commitment, reduces turnover intentions, and increases employee loyalty.…”
Section: Financial Rewards and Employee Commitmentmentioning
confidence: 99%
“…Suggestions further research to conduct research on the direct influence of employee development on employee performance, which was not carried out in this study. Then can also add employee loyalty variables as in the research conducted by Urbancová and Vnoučková, (2018) which states that employee development significantly affects commitment, loyalty and employee performance.…”
Section: Discussionmentioning
confidence: 99%
“…So it is necessary for companies to invest a lot of funds to develop their employees. Based on the research of (Urbancová and Vnoučková, 2018) which states that employee development significantly affects commitment, loyalty, and employee performance, it can be concluded that the provisional hypothesis that became the formulation of the research above, namely: H6: talent management has an effect on employee performance mediated by employee development.…”
Section: Theoritical Reviewmentioning
confidence: 99%